The new America's wonderlands : our National Parks - National Geographic Book Service; Bennett, Ross S. (Washington : National Geographic Society, 1980)
Text and color photographs highlight the natural beauty of the more than 300 United States national parks and describes efforts to promote the preservation of these areas.
Includes index.
Keywords: National parks and reserves -- United States; National parks and reserves; United States -- Description and travel; United States -- Description and travel